(untitled) (Revista de Educação Pública, 2014)
Reitora • Chancellor Maria Lúcia Cavalli Neder Vice-Reitor • Vice-Chancellor João Carlos de Souza Maia Coordenadora da EdUFMT • EdUFMT’s Coordinator Lúcia Helena Vendrúsculo Possari